Spatial and temporal patterns of richness and abundance in the anuran assemblage of an artificial water reservoir from the semiarid central region of Argentina - Jofré, Mariana (2010)
This constitutes the first study of anuran fauna composition of an artificial permanent water reservoir, in a semiarid ecosystem of San Luis. Species richness, relative abundance, spatial distribution and pattern of summer activity were estimated in the anuran community of the Embalse La Florida, an artificial water reservoir in the semiarid central region of the sierras of San Luis, Argentina. This reservoir represents one of the few sources of water available for reproduction and early development of amphibian species in the zone. We identified anurans using call surveys during two summers at fifteen sites, belonging to four zones around the shorelines of the reservoir. Eight amphibian species (Rhinella arenarum, Melanophryniscus stelzneri, Leptodactylus bufonius, Leptodactylus mystacinus, Odontophrynus americanus, Odontophrynus occidentalis, Pleurodema tucumanum and Hypsiboas cordobae) were recorded at the shores of the embalse. The highest species richness (seven) was detected in the preserve located on the north shore. Species richness analyzed by month or survey was not correlated with weather variables. The highest relative abundance of anurans was detected at the highly modified campsites area, which may provide stable food and refugia. Relative abundance of all anuran species was positively correlated with precipitation. This permanent water reservoir may act as an important site of amphibian fauna concentration, which is important to monitor and preserve.